Immune checkpoint inhibitors in cancer therapy: what lies beyond monoclonal antibodies? - Zamani, Mohammad Reza; Šácha, Pavel (Medical oncology (Northwood, London, England), 2025)
Immune checkpoints are critical in modulating immune responses and maintaining self-tolerance. Cancer cells can exploit these mechanisms to evade immune detection, making immune checkpoints attractive targets for cancer therapy. The introduction of immune checkpoint inhibitors (ICIs) has transformed cancer treatment, with monoclonal antibodies targeting CTLA-4, PD-1, and PD-L1 demonstrating clinical success. However, challenges such as immune-related adverse events, primary and acquired resistance, and high treatment costs persist. To address these challenges, it is essential to explore alternative strategies, including small-molecule and peptide-based inhibitors, aptamers, RNA-based therapies, gene-editing technologies, bispecific and multispecific agents, and cell-based therapies. Additionally, innovative approaches such as lysosome-targeting chimeras, proteolysis-targeting chimeras, and N-(2-hydroxypropyl) methacrylamide copolymers are emerging as promising options for enhancing treatment effectiveness. This review highlights significant advancements in the field, focusing on their clinical implications and successes.
Keywords: Immune checkpoint inhibitors; imunoterapie; inhibitory kontrolních bodů; Immunotherapy; Cancer therapy; Monoclonal antibodies; nádory; monoklonální protilátky; Antibodies, Monoclonal; Animals; lidé; Neoplasms; Immune Checkpoint Inhibitors; Humans; zvířata; Small molecules